Mac OS X Lion Made Simple - Congress, Axely; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
So you have your brand new Mac, or perhaps you've upgraded to Lion on an existing desktop or laptop. Now what? OS X Lion Made Simple will guide you through all of the new features of Lion, as well as provide a thorough tour of the features and applications that are OS X standards. You'll discover how to make the most of features like Spotlight, Stacks, and Air Drop, and you'll see how to get the newest version of Mail working exactly the way you want it to. Inside this book, you will find all of the new features of OS X Lion explained, exposed, and uncovered. It's filled with clear and colorful images that help you get the bigger picture and get a close-up look at what OS X Lion has to offer. Whether you are just joining the many millions of Mac users around the world, or you are upgrading from Snow Leopard, this book will assist you in uncovering the many new options offered with OS X Lion.
Keywords: Computer science; Computer Science; Computer Science, general